Serum miRNA‐122 in acute liver injury induced by kidney injury and sepsis in CD‐1 mouse models. Issue 13 (29th March 2015) - Leelahavanichkul, Asada; Somparn, Poorichaya; Panich, Thanaporn; Chancharoenthana, Wiwat; Wongphom, Jutamas; Pisitkun, Trairak; Hirankarn, Nattiya; Eiam‐Ong, Somchai
Abstract: Aim: miRNA‐122 (miR‐122) is a new, interesting liver injury biomarker but little is known about its effects when there is an indirect acute liver injury. Methods: We investigated this by using indirect liver injury mice models with bilateral ureter obstruction (BUO), bilateral nephrectomy (BiNx) and cecal ligation and puncture (CLP). A direct liver injury model, liver ischemia/reperfusion injury (liver I/R), was performed in parallel. Liver injury (i.e. liver histology, alanine transaminase [ALT]), kidney damage (i.e. serum creatinine) and cytokines (i.e. tumor necrosis factor‐α, interleukin [IL]‐6, IL‐1β, IL‐10) were assessed. Results: Six hours after BUO/BiNx/CLP, the ALT and serum cytokines were approximately 1.5‐fold higher than the baseline whereas miR‐122 did not change. After 6 h of BiNx, there were prominent hepatocyte vacuolization but no elevations of miR‐122. However, after 24 h of BUO/BiNx/CLP, ALT, hepatocyte vacuolization and miR‐122 increased. The cytokines at 6 h might have induced the production of miR‐122 at 24 h. The results from the in vitro study with HepG2 cells and each of the cytokines resulted in increased miR‐122. On the other hand, when the direct liver injury model was used, there was a fivefold and 22‐fold increase in the ALT at 0.5 and 1 h after surgery, respectively, and high serum miR‐122 which corroborated the results from the liver histopathology. Conclusion: We demonstrated that prior serum cytokine accumulation increased serum miR‐122 in indirect liver injury induced by BUO/BiNx and less severe sepsis mouse models. Cytokine accumulation may be responsible for miR‐122 expression in these models. The clinical importance of liver injury demonstrated by the discordance between serum miR‐122 and ALT was an interesting issue.